The Implications of Learning The Science of Kalam and Its Ideology for Children - Suryani, Ira; Ningsih, Titik (Universitas Pahlawan Tuanku Tambusai, 2022)
The science of kalam is a fundamental study that must be taught to children from the ground up. Of course, the teaching in question is adjusted to the phase or stage of the child's development. This study aims to analyze the implications of studying the flow of kalam and its ideology for children. The research method used is qualitative research with literature study method. sources of information and analysis efforts using scientific data based on literature or up-to-date references, including articles, books, proceedings, and final assignments (thesis, thesis, dissertation). The results of this study indicate that studying kalam and its ideology is not a taboo for children. Because, the more children know the Almighty God according to their developmental phase, the more children will reflect the noble character from an elementary age. This is reflected in the attitudes and values of tolerance inherent in children.